Economic Preconditions for the Development of Public-Private Partnership in the Vologda Region - Irina Mikhaylovna Statsenko (Экономика региона, 2018)
The partnership of the state and business is one of the powerful tools for solving socially significant tasks of a region. The annual rankings of regions as regards the level of public-private partnership development do not take sufficient account of the initial economic and investment conditions for the development of regions. Moreover, it hampers assessing the effectiveness of the regional authorities in the sphere of public-private partnership. Therefore, the identification of economic preconditions stimulating or, on the contrary, restraining the development of public-private partnership in the subjects of the Russian Federation is relevant. The article describes the main trends in the development of public-private partnership in the Vologda region. The study is based on the rating assessments of the level of public-private partnership development in the regions of the Russian Federation, as well as on the socio-economic ranking of regions and the rating of their investment potential and risk. To achieve the goal of the study, the methods of dynamic analysis, modelling, and structural analysis as well as statistical methods are used in the article. The research has shown a strong correlation dependence of the development of public-private partnership in the region on its economic and investment situation. The Vologda region ranked 29th place in the public-private partnership development rating in 2016. I substantiate that the region should occupy 44th place in this rating taking into account economic and investment conditions, and under the optimistic scenario, it could take the 9th place. It indicates the reserves for the development of the public-private partnership in the region. The author’s coefficient of the application of economic and investment conditions for the development of public-private partnership in the Vologda region is 1.52, which indirectly confirms the effectiveness of government decisions in the sphere of public-private partnership. Further research in the field of the formation of conceptual bases for the public-private partnership development taking into account the industrial features of the Vologda region will contribute to the development of public-private partnership in the Vologda region.